Comparisons Between Bacterial Communities in Mucosa in Patients With Gastric Antrum Ulcer and a Duodenal Ulcer - Chen, Xia; Xia, Chenmei; Li, Qianqian; Jin, Linxiao; Zheng, Liyun; Wu, Zhongbiao (Frontiers in Cellular and Infection Microbiology, 2018)
Objective To identify and compare the bacterial community profile of mucosal tissues from a gastric antrum ulcer and a duodenal ulcer in Helicobacter pylori (HP) positive dyspeptic patients. Methods Genomic DNA was extracted from the mucosal tissues obtained from eighteen patients diagnosed with gastric antrum or duodenal ulcers. A library was constructed using 16S rRNA gene amplification, and Miseq high-throughput sequencing was used to analyse the amplified products. Bioinformatics methods, including operational taxonomic units (OTUs), hierarchical clustering, and a diversity analysis, were performed to investigate and characterize the community composition. Results The proportion of Helicobacter in the mucosa of patients with a gastric antrum ulcer was significantly higher than that of patients with a duodenal ulcer. However, the diversity of the bacterial community in the gastric antrum ulcer mucosa was significantly lower compared with the mucosa of the duodenal ulcer. There were significant differences in microbial community structure between the gastric antrum ulcer and the duodenal ulcer. Notably, Helicobacter, Prevotella, Neisseria and Streptococcus were also predominant genera in the bacterial community of the duodenal ulcer mucosa, and they outnumbered those species in gastric antrum ulcer mucosa. Conclusion The bacterial community composition and the corresponding abundance differ between the mucosal tissues of HP positive gastric antrum ulcer and duodenal ulcer patients. Additionally, the bacterial community diversity in the mucosal tissues from gastric duodenal ulcer patients is higher than that from gastric antrum ulcer patients, and Helicobacter is not the absolutely predominant genus.